1985
DOI: 10.1007/bf00393508
|View full text |Cite
|
Sign up to set email alerts
|

Potassium transport in Chlamydomonas reinhardtii: isolation and characterization of transport-deficient mutant strains

Abstract: Putative potassium-transport-deficient mutant strains of Chlamydomonas reinhardtii Dang. were induced by ultra-violet mutagenesis and were identified by their dependence on abnormally high concentrations of potassium for growth. Potassium transport studies employing (86)Rb as a tracer were carried out with wild-type cells and with three independently isolated KDP (potassium-dependent phenotype) clones. Wildtype cells exhibit two transport activities. Transport activity A was expressed when cells were grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…coli (Rhoads et al, 1977). This discrimination against "Rb+ in Chlamydomonas was reported earlier by Polley and Doctor (1985). These authors also observed that the extent of the K+/Rb+ selectivity increased with K+ starvation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…coli (Rhoads et al, 1977). This discrimination against "Rb+ in Chlamydomonas was reported earlier by Polley and Doctor (1985). These authors also observed that the extent of the K+/Rb+ selectivity increased with K+ starvation.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study (Polley and Doctor, 1985), K+("Rb+) influx in C. reindavdtii over the range from O to 6 mM was described by a single Michaelis-Menten curve. In the present study, the influx isotherm for K'(4ZK+ and "Rb+) influx was resolved into a biphasic pattern, with saturable and nonsaturable components.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The second approach has so far mainly been used with bacterial and fungal cells (18) and only to some extent with human cells, in the analysis of hereditable diseases related to transport defects (18). Few studies have been made using transport mutants of plant cells (10,19).…”
mentioning
confidence: 99%